Impaired performance of the smash stroke in badminton induced by muscle fatigue - Le Mansec, Y.; Perez, J.; Rouault, Q.; Doron, J.; Jubeau, M. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To evaluate the effects of muscle fatigue on badminton performance during a smash stroke. Methods: In total, 17 young, well-trained players completed 20 forehand smashes twice (prefatigue and postfatigue protocol), and both speed and precision of the strokes were measured. The fatigue protocol consisted of 10 series of 10 maximal countermovement jumps (3-s rest in between) followed by 8 lunges. Perception of effort and countermovement-jump performance during each series were also measured to assess fatigue. Results: Shuttlecock speed decreased moderately (-3.3%) but significantly after the fatigue protocol (P<.001, 2p=.671). Precision significantly decreased after the fatigue protocol (-10.3%, P=.001, Eta2p=.473). The decrease in precision was mainly due to an increased number of faults (P=.006, Eta2p=.378, dz=0.756) and to a decrease in accuracy (P=.066, Eta2p=.195, dz=0.478). Conclusion: The present study showed that fatigue impairs performance during specific badminton skills. Moreover, by showing a slight decrease in speed and a large decrease in accuracy of the shuttlecock when fatigue is experienced, the present study suggested that, as previously observed in other racket sports, the speed of the missile appears to be the key factor used by the players to win the rally. Coaches and physical trainers should therefore develop interventions aiming to limit the negative impact of fatigue on badminton strokes.